From Industrial Organization to Entrepreneurship A Tribute to David B. Audretsch - Lehmann, Erik E.; Keilbach, Max (Springer International Publishing : Imprint: Springer, 2019)
XII, 488 p. 42 illus., 30 illus. in color.